6(1.3k-4.6)=11.4

Simple and best practice solution for 6(1.3k-4.6)=11.4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(1.3k-4.6)=11.4 equation:


Simplifying
6(1.3k + -4.6) = 11.4

Reorder the terms:
6(-4.6 + 1.3k) = 11.4
(-4.6 * 6 + 1.3k * 6) = 11.4
(-27.6 + 7.8k) = 11.4

Solving
-27.6 + 7.8k = 11.4

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '27.6' to each side of the equation.
-27.6 + 27.6 + 7.8k = 11.4 + 27.6

Combine like terms: -27.6 + 27.6 = 0.0
0.0 + 7.8k = 11.4 + 27.6
7.8k = 11.4 + 27.6

Combine like terms: 11.4 + 27.6 = 39
7.8k = 39

Divide each side by '7.8'.
k = 5

Simplifying
k = 5

See similar equations:

| 4-2y-y=12-4 | | 13x+11x+x=1520 | | 5x^2+2x=24 | | 0.7x-0.6(5-2x)=-0.9(x-6) | | 6x+8+3(m+2)=12.6 | | -6(y-2y)+2=-6(3y-y)+9+17y | | 7p+12=13+5p | | VAR(4-3Z)=0 | | x^5-x^4-2x^3+2x^2+24=0 | | Y=.50x-100 | | 4z-a=3 | | y=x^9/x^13 | | 12/5(r-2)=2/3(3r-2(2r-1)) | | y=(7x-1)(x+3) | | y=(7x+1)(x-3) | | -3(y-4)=-5(y+2) | | x=(7x+1)(x-3) | | 5*4/8*-1/-7= | | 8y+6=-y-2 | | 11/1331 | | X=(y+6)(y+8) | | 75x^3+65x^2+10x=0 | | 5x+1y+0.05z=100 | | 31/2=62/t | | n/0.28=0.3/0.42 | | 18t=27(t-8) | | 16/19=p/13 | | (30/250)*5 | | 18t=17(t-8) | | 14/20=p/16 | | 8b^4(4b^3-7)= | | 14/8=28/m |

Equations solver categories